PENGARUH DISIPLIN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH (BKD) PROVINSI JAWA TENGAH - Miftahul Umam, 14.05.51.0057; Rozak, Hasan Abdul (Students' Journal of Economic and Management, 2018)
This research aims to examine and analyze the influence of the discipline, motivation, and the work environment on performance clerk Staffing Agency Area of Central Java province. The respondents of this study consists of 78 employees Staffing Agency Area of Central Java province. Model of data analysis used is test validity with product reliability test of the moment, with a Cronbach Alpha and multiple linear regression analysis using IBM SPSS software version 20.0 to test and prove the hypothesis of the study. Data collected after the test result all data stated is valid and reliable. The result of the analysis and discussion shows that: (1) Discipline work influential insignificant while negative on the employee performance.(2). the positive and significant effect of motivation against the performance of the employees, and (3). The work environment is positive and significant effect against the performance of employees. Simultaneously the discipline, motivation and work environment effect taking action against employee performance. Keyword : discipline, motivation, work environment, Employee Performance